Efek vortex generators terhadap peningkatan perpindahan panas pada aliran melewati heated tubes - Effendi, Yafid; Rosyidin, Ali (Universitas Muhammadiyah Metro, 2020)
In this decade, improving the rate of heat transfer has become a big challenge. The high thermal resistance of the gas side of the heat exchanger has an impact on the low rate of heat transfer. Therefore, an experimental study was carried out aimed at looking at conditions of hot temperature and decreased air flow pressure through a heated tube in a rectangular channel using artificial surfaces, namely the concave delta winglet and delta winglet vortex generators. Concave delta winglet vortex generators (CDW VGs) are installed in-line and staggered with one, and two pairs are arranged in common-flow-down (CFD) in the direction of flow with an angle of attack of 15o. The experimental results show that the best thermal performance is observed in the use of two rows CDW VGs staggered, where the value of performance evaluation criteria (PEC) is 28.88% higher than the use of CDW VGs in-line, DW VGs staggered and DW VGs in-line at the same Reynolds number. At the same Reynolds number, the Nusselt number ratio and the friction factor ratio increased 45.25% and 152.05% respectively, occurring in two rows of CDW VGs staggered compared to other vortex generators.Keywords: vortex generators, heat transfer, Nusselt number, friction factor, PECRasakan sensasi serunya bermain tanpa hambatan di situs link gacorqq, kesempatan mendapatkan jackpotnya cukup mudah dan sangat cepat.